Lubricating oil composition and preparation method thereof
By using modified plant polyphenol-based porous carbon and dialkyl dithiophosphoric acid in lubricating oil, the mechanical stability and compatibility problems of nanomaterials in lubricating oil are solved, and the resistance of lubricating oil is significantly improved Grinding performance and dispersion performance achieve better lubrication effect.
Patent Information
- Application Number
- CN202411462889.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-19
- Publication Date
- 2025-01-10
AI Technical Summary
The mechanical stability of nanomaterials in existing lubricating oils is weak, poor compatibility with base oil and easy to agglomerate, which affects its wear resistance.
Plant polyphenol-based porous carbon is used as the component of oil storage particles, and modified by dialkyl dithiophosphoric acid to enhance its lipophilicity, and combine metal salts, antioxidants and preservatives to form a lubricating oil composition.
It improves the wear resistance and dispersion performance of lubricating oil, ensures the integrity of the oil film and efficient self-lubricating, and significantly improves its lubricating performance at high temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lubricating oils, and in particular to a lubricating oil composition and a preparation method thereof. Background Art
[0002] Mechanical lubricants refer to lubricating materials used in various mechanical equipment to reduce friction loss, lower temperature, prevent oxidation, prevent corrosion, and clean the surface of the equipment. Lubricants must have excellent lubrication properties to reduce friction and wear inside mechanical equipment and extend the life of the machinery. Mechanical equipment is prone to generate heat during operation, and lubricants can take away some of the heat to keep the mechanical equipment at a normal operating temperature. Lubricants also have good anti-rust and anti-corrosion properties, which can prevent metal parts from being affected by oxidation and corrosion. Mechanical equipment is prone to generate high temperatures during operation, and lubricants have good high temperature resistance and can maintain normal lubrication properties even at high temperatures. Lubricants are widely used in various mechanical equipment, such as automobiles, ships, aircraft, generators, hydraulic systems, gearboxes, bearings, etc.
[0003] In the prior art, nanomaterials are widely used as functional nano-additives for lubricating oils due to their small size and surface effects, unique physical and chemical properties, and the ability to enter between friction pairs and interact with the surfaces of the friction pairs to reduce friction and resist wear. However, since they have no lipophilic groups and high surface energy, they have problems such as weak mechanical stability, poor compatibility with base oils, and easy self-agglomeration, which in turn affects the homogeneity of the lubricating oil and further affects its wear resistance. Summary of the invention
[0004] The purpose of the present invention is to provide a lubricating oil composition and a preparation method thereof to solve the following technical problems: How to improve the wear resistance of lubricating oil? The purpose of the present invention can be achieved through the following technical solutions: In a first aspect, the present invention discloses a lubricating oil composition, comprising the following components in parts by weight: 80-100 parts of base oil, 3-5 parts of oil storage particles, 1-2 parts of metal salt, 0.5-1 parts of antioxidant, 0.5-1 parts of preservative; Preferably, the base oil is 85-95 parts, the oil storage particles are 3.5-4.5 parts, the metal salt is 1.2-1.8 parts, the antioxidant is 0.6-0.9 parts, and the preservative is 0.6-0.9 parts; More preferably, the base oil is 90 parts, the oil storage particles are 4 parts, the metal salt is 1.5 parts, the antioxidant is 0.8 parts, and the preservative is 0.8 parts.
[0005] Furthermore, the oil storage particles include plant polyphenol-based porous carbon and dialkyl dithiophosphoric acid in a mass ratio of 100:(5-8); the mass ratio is preferably 100:6.
[0006] Furthermore, the plant polyphenol-based porous carbon is prepared according to the following steps: S1, dissolving the plant polyphenol powder evenly in tetrahydrofuran to form solution A, dissolving the nano silicon dioxide powder evenly in anhydrous ethanol to form solution B, and dissolving Pluronic F127 evenly in deionized water to form solution C; Furthermore, the mass ratio of plant polyphenols, nano-silicon dioxide powder and Pluronic F127 is 2:1:1.
[0007] Furthermore, the dosage ratio of the plant polyphenol powder to tetrahydrofuran in solution A is 1 g:(30-40) mL, preferably 1 g:35 mL.
[0008] Furthermore, the dosage ratio of the nano-silicon dioxide powder to anhydrous ethanol in solution B is 1 g: (20-30) mL, preferably 1 g: 25 mL.
[0009] Furthermore, the dosage ratio of Pluronic F127 to deionized water in solution C is 1 g: (20-30) mL, preferably 1 g: 25 mL.
[0010] S2. Mix solution A, solution B and solution C and stir for 10 hours, then dry and grind to obtain a mixed powder, pyrolyze the mixed powder to remove nano-silicon dioxide and Pluronic F127, and obtain a carbon matrix.
[0011] Furthermore, the mixed powder is pyrolyzed in a tubular furnace, heated from room temperature to 650°C in a nitrogen atmosphere for 20 minutes at a heating rate of 5°C / min, and finally cooled to room temperature in the furnace.
[0012] S3. Add the carbon matrix into a hydrofluoric acid solution and stir for 10 hours to acid-etch its mesopores. After filtering, wash the filter material with deionized water until the solution is neutral. Finally, dry and grind it to obtain plant polyphenol-based porous carbon.
[0013] In the preparation process of plant polyphenol-based porous carbon, nano-silica and Pluronic F127 are used as templates at the same time. During the pyrolysis process, the active groups in the plant polyphenol structural units will form micelles with the Pluronic F127 macromolecules through strong hydrogen bonds, which will cause the porous carbon to obtain more mesopores. At the same time, Pluronic F127 serves as the overall framework support, and nano-silica is evenly dispersed in the carbon substrate formed by plant polyphenols, which can make the mesopores highly ordered. After etching with hydrofluoric acid solution, the pore size of the highly ordered mesopores is adjusted to different degrees, so that the pores of the plant polyphenol-based porous carbon are rich and uniform and the size is distributed in multiple levels, which is beneficial to improving its oil storage performance.
[0014] Furthermore, the preparation method of the oil-storage particles is as follows: dissolving dialkyl dithiophosphoric acid in anhydrous ethanol to form a mixed solution, adding plant polyphenol-based porous carbon to the mixed solution, ultrasonically mixing at 60° C. for 1.5 hours, taking out and drying, and grinding to obtain oil-storage particles.
[0015] Dialkyl dithiophosphoric acid is composed of thiophosphate and long-chain alkane, and has excellent tribological properties. The thiophosphate group is bonded to the phenolic hydroxyl group in the plant polyphenol-based porous carbon under the action of ultrasound, so that the dialkyl dithiophosphoric acid is fixed on the outer surface and the inner wall of the pores of the plant polyphenol-based porous carbon, while the alkyl chain in the dialkyl dithiophosphoric acid is exposed to the outside, thereby enhancing the lipophilicity of the plant polyphenol-based porous carbon and improving its dispersion performance in the base oil.
[0016] Furthermore, the ratio of the mixed solution of dialkyl dithiophosphoric acid to anhydrous ethanol is 1 g:(5-10) mL, preferably 1 g:8 mL.
[0017] Furthermore, the metal salt is a mixture of any one of alkylnaphthalenesulfonate barium salt or alkylbenzenesulfonate calcium salt or both in any ratio.
[0018] Preferably, the metal salt is a mixture of metal salt alkylnaphthalenesulfonate barium salt and alkylbenzenesulfonate calcium salt in a mass ratio of 1:2.
[0019] Furthermore, the antioxidant is any one of hindered amines, dioctyl diphenylamine, butyl octyl diphenylamine, dinonyl diphenylamine, and sulfide diphenylamine, or a mixture of any multiple thereof in any proportion.
[0020] Preferably, the antioxidant is a hindered amine.
[0021] Furthermore, the preservative is any one of lead cyclopentaneate, phenothiazine, disalicylidenepropylenediamine, sodium benzoate, polyisobutylene, and calcium carbonate, or a mixture of any multiple thereof in any proportion.
[0022] Preferably, the preservative is lead naphthenate.
[0023] Based on this, a preferred lubricating oil composition of the present invention can be obtained, which includes 90 parts of base oil, 4 parts of oil storage particles, 0.5 parts of alkylnaphthalenesulfonic acid barium salt, 1 part of alkylbenzenesulfonic acid calcium salt, 0.8 parts of hindered amine, and 0.8 parts of lead naphthenate in parts by weight; in: The preparation method of the oil storage particles is as follows: dissolving dialkyl dithiophosphoric acid in anhydrous ethanol to form a mixed solution (the mass ratio of dialkyl dithiophosphoric acid to anhydrous ethanol is 1 g: 8 mL), adding plant polyphenol-based porous carbon to the mixed solution (the mass ratio of plant polyphenol-based porous carbon to dialkyl dithiophosphoric acid is 100: 6), ultrasonically mixing at 60° C. for 1.5 h, taking out and drying, grinding, and obtaining oil storage particles; The preparation method of plant polyphenol-based porous carbon is as follows: prepare plant polyphenols, nano-silica powder and Pluronic F127 in a mass ratio of 2:1:1, uniformly dissolve the plant polyphenol powder in tetrahydrofuran to form solution A (the ratio of plant polyphenol powder to tetrahydrofuran is 1 g:35 mL), uniformly dissolve the nano-silica powder in anhydrous ethanol to form solution B (the ratio of nano-silica powder to anhydrous ethanol is 1 g:25 mL), and uniformly dissolve Pluronic F127 in deionized water to form solution C (Pluronic F127). ronicF127 and deionized water in a ratio of 1g:25mL); solution A, solution B, and solution C are mixed and stirred for 10 hours, then dried and ground to obtain a mixed powder, the mixed powder is placed in a tubular furnace, heated from room temperature to 650°C under a nitrogen atmosphere and kept warm for 20 minutes at a heating rate of 5°C / min, and finally cooled to room temperature with the furnace to obtain a carbon matrix; the carbon matrix is added to a hydrofluoric acid solution and stirred for 10 hours, and after filtering, the filter material is washed with deionized water until the solution is neutral, and finally dried and ground to obtain plant polyphenol-based porous carbon.
[0024] Furthermore, the base oil is a mineral base oil or a synthetic base oil.
[0025] In a second aspect, the present invention further discloses a method for preparing the lubricating oil composition as described above, which is carried out according to the following steps: Firstly, the oil storage particles and the metal salt are added to the base oil and stirred evenly, and then the antioxidant and the preservative are added and stirred evenly to obtain the lubricating oil composition.
[0026] Beneficial effects of the present invention: 1. In the lubricating oil composition of the present invention, in the preparation process of the plant polyphenol-based porous carbon in the oil storage particles, nano-silicon dioxide and Pluronic F127 are used as templates at the same time. During the pyrolysis process, the active groups in the plant polyphenol structural units will form micelles with the Pluronic F127 macromolecules through strong hydrogen bonds, which promotes the porous carbon to obtain more mesopores. At the same time, Pluronic F127 serves as the overall framework support, and the nano-silicon dioxide is uniformly dispersed in the carbon substrate formed by the plant polyphenols, which can make the mesopores highly orderly arranged; after etching with a hydrofluoric acid solution, the pore size of the highly orderly arranged mesopores is adjusted to different degrees, so that the pores of the plant polyphenol-based porous carbon are rich and uniform and the size is multi-level distributed, which is beneficial to improving its oil storage performance.
[0027] 2. In the lubricating oil composition of the present invention, the surface of the plant polyphenol-based porous carbon in the oil storage particles is modified by dialkyl dithiophosphoric acid, which is composed of thiophosphate and long-chain alkane and has excellent tribological properties. The thiophosphate group is bonded to the phenolic hydroxyl group in the plant polyphenol-based porous carbon under the action of ultrasound, so that the dialkyl dithiophosphoric acid is fixed on the outer surface of the plant polyphenol-based porous carbon and the inner wall of the pores, while the alkyl chain in the dialkyl dithiophosphoric acid is exposed to the outside, thereby enhancing the lipophilicity of the plant polyphenol-based porous carbon and improving its dispersion performance in the base oil, so that the base oil can fully penetrate into the oil storage particles, and the oil storage particles can efficiently absorb and release the base oil to achieve self-lubrication, which is beneficial to maintain the integrity of the oil film when the oil film is formed, thereby further improving its wear resistance. DETAILED DESCRIPTION
[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0030] The following Pluronic F127 was purchased from Beijing Biolab Technology Co., Ltd. and has a molecular weight of 12.6 kDa.
[0031] Preparation Example 1 Preparation of plant polyphenol-based porous carbon.
[0032] Step 1: Dissolve 30 g of plant polyphenol powder in 1050 mL of tetrahydrofuran to form solution A, dissolve 15 g of nano-silicon dioxide powder in 375 mL of anhydrous ethanol to form solution B, and dissolve 15 g of Pluronic F127 in 375 mL of deionized water to form solution C; Step 2: Add solution A, solution B, and solution C into a stirring tank and mix and stir for 10 hours, then transfer to a vacuum drying oven and dry at 80°C for 12 hours, and then transfer to a ball mill to grind to obtain a mixed powder, place the mixed powder in a tubular furnace, heat from room temperature to 650°C in a nitrogen atmosphere and keep warm for 20 minutes, the heating rate is 5°C / min, and finally cool to room temperature with the furnace to obtain a carbon matrix; Step 3: Add the carbon matrix into the hydrofluoric acid solution and stir for 10 hours. Use a filter to filter, then wash the filter material with deionized water 5 times. The solution is neutral as measured by the pH meter. Then transfer it to a vacuum drying oven and dry it at 120°C for 3 hours. Transfer it to a ball mill and grind it to obtain plant polyphenol-based porous carbon. After weighing, the obtained plant polyphenol-based porous carbon is 29.12g.
[0033] Comparative Preparation Example 1 Preparation of plant polyphenol-based porous carbon.
[0034] Compared with Example 1, the only difference is that solution C is not prepared in step 1 and solution C is not added in step 2, and other conditions are exactly the same. Finally, plant polyphenol-based porous carbon is obtained. After weighing, the obtained plant polyphenol-based porous carbon is 29.45g.
[0035] Preparation Example 2 Preparation of oil storage particles.
[0036] In an ultrasonic mixer, 1.5 g of dialkyl dithiophosphoric acid was dissolved in 12 mL of anhydrous ethanol to form a mixed solution, to which 25 g of the plant polyphenol-based porous carbon prepared in Preparation Example 1 was added, and the mixture was ultrasonically mixed at 60 Hz at 60 ° C for 1.5 h. After being taken out, it was transferred to a vacuum drying oven and dried at 80 ° C for 6 h. Then, it was transferred to a ball mill for grinding to obtain oil storage particles.
[0037] Comparative Preparation Example 2 Preparation of oil storage particles.
[0038] Compared with Preparation Example 2, the only difference is that the plant polyphenol-based porous carbon prepared in Preparation Example 1 is replaced by the plant polyphenol-based porous carbon prepared in Preparation Example 2, and the other conditions are exactly the same, and finally oil-storing particles are obtained.
[0039] Comparative Preparation Example 3 4 g of the plant polyphenol-based porous carbon prepared in Preparation Example 1 was directly weighed as the oil storage particles of the control group.
[0040] Comparative Preparation Example 4 4 g of the plant polyphenol-based porous carbon prepared in Preparation Example 2 was directly weighed as the oil storage particles of the control group.
[0041] Example 1 The lubricating oil composition is prepared according to the most preferred lubricating oil composition component ratio of the present invention.
[0042] Add 90g of PAO base oil into a stirring tank, and then add 4g of the oil storage particles prepared in Preparation Example 2, 0.5g of alkylnaphthalenesulfonate barium salt, and 1g of alkylbenzenesulfonate calcium salt in sequence, and stir rapidly at 400r / min for 2h, then add 0.8g of hindered amine and 0.8g of lead cyclopentaneate, and continue to stir rapidly at 400r / min for 1.5h to obtain a lubricating oil composition.
[0043] Example 2 A lubricating oil composition is prepared.
[0044] Compared with Example 1, the only difference is that the amount of each component is different, specifically: 80g of base oil, 3g of oil storage particles obtained in Preparation Example 2, 0.5g of barium salt of alkylnaphthalenesulfonate, 0.5g of calcium salt of alkylbenzenesulfonate, 0.5g of hindered amine, and 0.5g of lead cyclopentaneate; other conditions are exactly the same, and finally a lubricating oil composition is obtained.
[0045] Example 3 A lubricating oil composition is prepared.
[0046] Compared with Example 1, the only difference is that the amount of each component is different, specifically: 85g of base oil, 3.5g of oil storage particles obtained in Preparation Example 2, 0.5g of alkylnaphthalenesulfonate barium salt, 0.7g of alkylbenzenesulfonate calcium salt, 0.6g of hindered amine, and 0.6g of lead cyclopentaneate; other conditions are exactly the same, and a lubricating oil composition is finally obtained.
[0047] Example 4 A lubricating oil composition is prepared.
[0048] Compared with Example 1, the only difference is that the amount of each component is different, specifically: 95g of base oil, 4.5g of oil storage particles obtained in Preparation Example 2, 0.9g of barium salt of alkylnaphthalenesulfonate, 0.9g of calcium salt of alkylbenzenesulfonate, 0.9g of hindered amine, and 0.9g of lead cyclopentaneate; other conditions are exactly the same, and a lubricating oil composition is finally obtained.
[0049] Example 5 A lubricating oil composition is prepared.
[0050] Compared with Example 1, the only difference is that the amount of each component is different, specifically: 100g of base oil, 5g of oil storage particles prepared in Preparation Example 2, 1g of alkylnaphthalenesulfonate barium salt, 1g of alkylbenzenesulfonate calcium salt, 1g of hindered amine, and 1g of lead cyclopentaneate; other conditions are exactly the same, and finally a lubricating oil composition is obtained.
[0051] Comparative Example 1 Compared with Example 1, the only difference is that the oil storage particles prepared in Preparation Example 2 are replaced by the oil storage particles prepared in Comparative Preparation Example 2, and other conditions are exactly the same, and finally a lubricating oil composition is obtained.
[0052] Comparative Example 2 Compared with Example 1, the only difference is that the oil storage particles prepared in Preparation Example 2 are replaced by the oil storage particles prepared in Comparative Preparation Example 3, and other conditions are exactly the same, and finally a lubricating oil composition is obtained.
[0053] Comparative Example 3 Compared with Example 1, the only difference is that the oil storage particles prepared in Preparation Example 2 are replaced by the oil storage particles prepared in Comparative Preparation Example 4, and other conditions are exactly the same, and finally a lubricating oil composition is obtained.
[0054] First, the dispersibility of the oil storage particles in the lubricating oil compositions prepared in Examples 1-5 and Comparative Examples 1-3 in the base oil was tested. The testing method was as follows: 20 mL of the wear-resistant lubricating oil prepared in Examples 1-5 and Comparative Examples 1-3 were respectively placed in test tubes and numbered, and left to stand for a period of time. The stratification of different density components in the lubricating oil was visually observed, and the observation was recorded every 24 hours to determine the dispersion effect. The observation results of the test are listed in Table 1, which is shown below: Table 1
[0055] By analyzing the data in Table 1, it can be seen that after standing for 120 hours, the lubricating oil compositions prepared in Examples 1-5 showed no precipitation and stratification phenomenon at all, which indicates that the oil storage particles in the lubricating oil composition of the present invention have a good dispersion effect in the base oil; Comparative Example 1 also showed no trace precipitation after standing for 120 hours, while Comparative Examples 2-3 showed a large amount of precipitation after standing for 48 hours, and completely precipitated after 72 hours, which indicates that the addition of dialkyl dithiophosphoric acid increases the lipophilicity of the polyphenol-based porous carbon and makes it more dispersible in the base oil.
[0056] Then, the lubricating oil compositions prepared in Examples 1-5 and Comparative Examples 1-3 were tested for wear resistance, and the test method was as follows: The wear test was carried out using a high-temperature multifunctional friction and wear tester (MMU-10G) and disc-pin friction. The test pin-disc was assembled and fixed by upper and lower fixtures. The relative speed between the pin and the disc was provided by a driving motor. The lower fixture contained an oil sample of the lubricating oil composition required for the test. The sliding screw was controlled by a computer to move upward to obtain the corresponding test force. The friction coefficient was calculated from the ratio of the friction torque measured by the torque sensor to the test radius.
[0057] The test results are listed in Table 2, which is as follows: Table 2
[0058] From the analysis of the data in Table 2, it can be seen that the average friction coefficient of the lubricating oil composition prepared in Examples 1-5 is significantly better than that of the lubricating oil composition prepared in Comparative Examples 1-3, which indicates that the lubricating oil composition of the present invention has more excellent wear resistance.
[0059] Specifically: 1. The test results of Comparative Example 1 and Example 1 are compared. In Comparative Example 1, the plant polyphenol-based porous carbon in the oil storage particles only uses nano-silicon dioxide as a single template during the preparation process. In Example 1, the plant polyphenol-based porous carbon in the oil storage particles uses nano-silicon dioxide and Pluronic F127 as a dual template during the preparation process. It can be shown that the regulation of Pluronic F127 is beneficial to improving the mesoporous properties of the oil storage particles, thereby affecting their wear resistance; 2. The test results of Comparative Example 2 and Example 1 are compared. In Comparative Example 1, the plant polyphenol-based porous carbon in the oil storage particles is not modified by dialkyl dithiophosphoric acid, while in Example 1, the plant polyphenol-based porous carbon in the oil storage particles is modified by dialkyl dithiophosphoric acid. This indicates that dialkyl dithiophosphoric acid improves the dispersion by enhancing the surface lipophilicity of the oil storage particles, thereby affecting their wear resistance. 3. The test results of Comparative Example 3 were compared with those of Example 1, Comparative Example 1 and Comparative Example 2. In Comparative Example 3, the plant polyphenol-based porous carbon in the oil storage particles only used nano-silica as a single template and was not modified by dialkyl dithiophosphoric acid. In Example 1, the plant polyphenol-based porous carbon in the oil storage particles used nano-silica and Pluronic F127 as dual templates during the preparation process and was modified by dialkyl dithiophosphoric acid, which can further confirm the conclusions of 1-2 above, indicating that the regulation of Pluronic F127 and the modification of dialkyl dithiophosphoric acid are important conditions for improving the wear resistance of the lubricating oil composition of the present invention.
[0060] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.
Claims
1. A lubricating oil composition, characterized in that: The composition comprises the following components in parts by weight: 80-100 parts of base oil, 3-5 parts of oil storage particles, 1-2 parts of metal salt, 0.5-1 parts of antioxidant, 0.5-1 parts of preservative; The oil storage particles include plant polyphenol-based porous carbon and dialkyl dithiophosphoric acid in a mass ratio of 100:(5-8).
2. The lubricating oil composition according to claim 1, characterized in that The preparation method of the oil storage particles is as follows: dissolving dialkyl dithiophosphoric acid in anhydrous ethanol to form a mixed solution, adding plant polyphenol-based porous carbon to the mixed solution, ultrasonically mixing at 60° C. for 1.5 hours, taking out and drying, grinding, and obtaining the oil storage particles.
3. The lubricating oil composition according to claim 2, characterized in that The ratio of the dialkyl dithiophosphoric acid to anhydrous ethanol in the mixed solution is 1 g: (5-10) mL.
4. The lubricating oil composition according to claim 1, characterized in that The plant polyphenol-based porous carbon is prepared according to the following steps: Step 1: Dissolve the plant polyphenol powder evenly in tetrahydrofuran to form solution A, dissolve the nano silicon dioxide powder evenly in anhydrous ethanol to form solution B, and dissolve Pluronic F127 evenly in deionized water to form solution C; Step 2: Mix solution A, solution B and solution C for 10 hours, then dry and grind to obtain a mixed powder, and pyrolyze the mixed powder to obtain a carbon matrix; Step 3: Add the carbon matrix into a hydrofluoric acid solution and stir for 10 hours. After filtering, wash the filter material with deionized water until the solution is neutral. Finally, dry and grind it to obtain plant polyphenol-based porous carbon.
5. The lubricating oil composition according to claim 4, characterized in that In the first step: the dosage ratio of plant polyphenol powder to tetrahydrofuran in solution A is 1g:(30-40)mL; the dosage ratio of nano-silicon dioxide powder to anhydrous ethanol in solution B is 1g:(20-30)mL; the dosage ratio of Pluronic F127 to deionized water in solution C is 1g:(20-30)mL.
6. The lubricating oil composition according to claim 4, characterized in that In the second step, the mixed powder is pyrolyzed by placing the mixed powder in a tubular furnace, heating it from room temperature to 650°C in a nitrogen atmosphere for 20 min at a heating rate of 5°C / min, and finally cooling it to room temperature with the furnace.
7. The lubricating oil composition according to claim 1, characterized in that The metal salt is any one of alkylnaphthalenesulfonate barium salt or alkylbenzenesulfonate calcium salt or a mixture of two of them in any ratio.
8. The lubricating oil composition according to claim 1, characterized in that The antioxidant is any one of hindered amines, dioctyl diphenylamine, butyl octyl diphenylamine, dinonyl diphenylamine, and sulfided diphenylamine, or a mixture of any multiple thereof in any proportion.
9. The lubricating oil composition according to claim 1, characterized in that: The preservative is any one of lead naphthenate, phenothiazine, disalicylidenepropylenediamine, sodium benzoate, polyisobutylene, and calcium carbonate, or a mixture of any multiple thereof in any proportion.
10. A method for preparing a lubricating oil composition according to any one of claims 1 to 9, characterized in that: Follow these steps: Firstly, the oil storage particles and the metal salt are added to the base oil and stirred evenly, and then the antioxidant and the preservative are added and stirred evenly to obtain the lubricating oil composition.